Geographical concepts and principles: theoretical-methodological elements for teaching geography in basic education - Luz Neto, Daniel Rodrigues Silva (Revista Ensino de Geografia (Recife), 2023)
The objective of this work is to discuss theoretical and methodological elements for the development and mobilization of students' geographic thinking in Basic Education. Therefore, it appropriates the qualitative approach as a theoretical discussion direction for the production of research results. Thus, a bibliographical research was carried out on geographic thought, concepts and logical principles. The research is articulated in three central axes: geographic thinking in Basic Education, geographic concepts and principles. The results showed that geographic concepts and principles are constituent elements of geographic thinking to be developed and mobilized by students in Basic Education. Therefore, such concepts and logical principles are indicated as guides for the teaching and learning process in Geography in Basic Education.